Coupling life cycle assessment and global sensitivity analysis to evaluate the uncertainty and key processes associated with carbon footprint of rice production in Eastern China - Xu, Qiang; Li, Jingyong; Liang, Hao; Ding, Zhao; Shi, Xinrui; Chen, Yinglong; Dou, Zhi; Dai, Qigen; Gao, Hui (Frontiers in Plant Science, 2022)
Graphical Abstract